Conversion of beams in the plasma lens and investigation of Z-pinch dynamics - Drozdowskiy, A.A.; Drozdowskiy, S.A.; Golubev, A.A.; Sasorov, P.V.; Savin, S.M.; Yanenko, V.V. (Вопросы атомной науки и техники, 2013)
The plasma lens can carry out sharp focusing of ion beam. At stages of the plasma discharge at which the magnetic field is nonlinear, formation of other configurations of beams is possible. The discharge current distributions obtained by calculation ensure the experiment. Possibility of the research of the plasma discharge dynamics by means of relativistic ions beams is shown. Плазмові лінзи можуть здійснювати не тільки гостре фокусування іонного пучка на тих етапах плазмового розряду, на яких магнітне поле є нелінійним, можливе формування інших цікавих конфігурацій іонного пучка. Розроблено чисельну методику отримання розподілу струму в плазмовій лінзі, адекватну фокусуючим властивостям лінзи. Продемонстрована можливість дослідження динаміки плазмового розряду за допомогою релятивістських пучків іонів. Плазменные линзы могут осуществлять не только острую фокусировку ионного пучка на тех этапах плазменного разряда, на которых магнитное поле является нелинейным, возможно формирование других интересных конфигураций ионного пучка. Разработана численная методика получения распределения тока в плазменной линзе, адекватная фокусирующим свойствам линзы. Продемонстрирована возможность исследования динамики плазменного разряда с помощью релятивистских пучков ионов.